Analisis Pembelajaran Menulis Permulaan Menggunakan Metode Titik Koding di TK Bhakti Kencana - Amy Rahayu Nurlia (UNISBA Press, 2022)
Abstract. This study aims to determine the learning process of beginning writing using the coding point technique which is a new technique and its implications for the development of students' initial writing skills at Bhakti Kencana Kindergarten. This type of research is qualitative. This research was conducted on six Bhakti Kencana Kindergarten (TK) students. To collect data, the researcher used observation, document analysis and interviews with open-ended questions to obtain more valid and accurate additional information and data related to learning to write beginning using the coding point technique and its implications for the students' initial writing ability. The results showed that 66% of students had very good developmental abilities, 22% of students developed according to expectations and 22% of students were still developing. The factor for the most mistakes made by students in writing the beginning is the factor of knowing the relationship between the sound and the shape of the letters. While the least error factor made by students is the factor of recognizing letters and imitating writing. In conclusion, this coding point technique is quite effective for use when learning to write beginning with the target of achieving recognition and imitating letters only, but less effective for making students understand the relationship between letter shapes and sounds. Researchers suggest that teachers know the learning achievement targets and adapt them to the learning techniques that will be used in the classroom. Abstrak.Penelitian ini bertujuan untuk mengetahui proses pembelajaran menulis permulaan menggunakan teknik titik koding yang merupakan teknik baru beserta implikasinya terhadap perkembangan kemampuan menulis permulaan siswa di TK Bhakti Kencana. Jenis penelitian ini adalah kualitatif. Penelitian ini dilakukan pada enam siswa Taman Kanak – Kanak (TK) Bhakti Kencana. Untuk mengambil data, peneliti menggunakan observasi, analisis dokumen dan wawancara dengan pertanyaan terbuka untuk mendapatkan informasi dan data tambahan yang lebih valid dan akurat terkait pembelajaran menulis permulaan menggunakan teknik titik koding dan implikasinya terhadap kemampuan menulis permulaan siswa tersebut. Hasil penelitian menunjukkan bahwa 66% siswa memiliki kemampuan Berkembang Sangat Baik, 22% siswa Berkembang Sesuai Harapan dan 22% siswa Masih Berkembang. Adapun Faktor kesalahan terbanyak yang dilakukan oleh siswa dalam menulis permulaan adalah faktor mengetahui hubungan antara bunyi dan bentuk huruf. Sedangkan faktor kesalahn paling sedikit yang dilakukan siswa adalah faktor mengenal huruf dan meniru tulisan. Kesimpulannya, teknik titik koding ini cukup efektif untuk digunakan saat pembelajaran menulis permulaan dengan target pencapaian pengenalan dan meniru huruf saja, tetapi kurang efektif untuk membuat siswa memahami hubungan bentuk dan bunyi huruf. Peneliti menyarankan agar guru – guru mengetahui target pencapaian pembelajaran dan menyesuaikannya dengan teknik pembelajaran yang akan digunakan di kelas.